Investigation on the mechanical properties and environmental impacts of pervious concrete containing fly ash based on the cement-aggregate ratio. (30th March 2019) - Wang, Hanbing; Li, Hui; Liang, Xiao; Zhou, Haonan; Xie, Ning; Dai, Zhen
Highlights: Explore the influences of cement-aggregate ratio (C/A) on pervious concrete. Identify an optimum range of C/A for pervious concrete with higher strength. 20% fly ash content possessed superior strength and fine purification effect. Introduce zebrafish biotoxicity test to detect the biotoxicity of percolate. Only disposed percolate could be used for rainwater recycling directly. Abstract: Pervious concrete is one kind of concrete with a larger porosity than dense concrete, usually in the range of 15–25%. It helps mitigate stormwater runoff, purify water and reduce the influence of splash on drivers through its porous structure. Nevertheless, the high porosity also has led to structural and environmental defects, especially low strength and the applicability of pervious concrete containing waste for rainwater recycling. This study firstly presented an adequate experimental investigation on the influences of the cement-aggregate ratio (C/A, by mass) on porosity, compressive strength of pervious concrete samples and determined an optimum C/A for higher compressive strength. Secondly, fly ash was chosen as supplementary cementitious material to replace Portland cement at the optimum C/A. Then a series of environmental investigation like Suspended Solids, Ammonia-nitrogen, Total Phosphorus, Alkali precipitation tests were carried out to explore the purifying effect of concrete samples. Finally, this paper introduced zebrafish acute biotoxicity test specially to evaluate whether pervious concrete containing fly ash could be used for runoff pollution controlling and rainwater recycling. According to the results, C/A has a significant influence on the properties of pervious concrete. C/A (0.20–0.24) and 20% fly ash content were recommended to produce high strength pervious concrete. Meanwhile, the percolate collected from pervious concrete containing fly ash showed acute toxicity, killed all the zebrafish within 20 min and the disposed percolate performed much better which means only the disposed percolate could be used for pavement construction and rainwater recycling.